The invention of human nature: the intention and reception of Pufendorf's entia moralia doctrine. Issue 7 (3rd October 2019) - Hunter, Ian
ABSTRACT: In treating human nature as a 'moral entity', imposed by God for reasons into which man could have no direct insight, Samuel Pufendorf reconfigured the architecture of natural law thought in a fundamental way. For this meant that rather than deducing norms from a nature in which they had been embedded by God and could be discerned by self-reflective reason, man had to derive them by observing the requirements of the exigent condition in which he happened to find himself; and it further meant that such observation would be gathered via erudite citation of humanist authorities, rather than from philosophical reflection or introspection. As a result of this reconstruction, Pufendorfian natural law was opened to the normative structure of historically existing juridical-constitutional orders, for which it supplied both a propaedeutic and an abstract rationale. At the same time, however, theological and philosophical forms of natural law, based on normative moral anthropologies, continued unabated, this giving rise to a partitioning of the field into an introspective philosophy of law, and an observational legal humanism.